The Relationship of Facial Skin Personal Hygiene to The Onset of Acne (Acne Vulgaris) in Adolescent Boys - Damayanti, Indah Sri; Minerva, Prima (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Acne is a common problem that often occurs at a young age and is influenced by factors such as climate, hygiene, cosmetic use, age, race, diet, gender, and genetics. This research was conducted at SMAN 1 Pangkalan Koto involving 155 male students. Of these, 111 students (71%) experienced acne problems. The purpose of the study was to assess the relationship between facial skin hygiene (Personal Hygiene) with the incidence of acne vulgaris in adolescent boys at SMAN 1 Pangkalan Koto Baru. The research method used is correlation analytics with a cross-sectional design. The independent variable is personal hygiene, while the dependent variable is the incidence of acne vulgaris. The study sample consisted of male students who had acne vulgaris and met the research criteria. Primary and secondary data were collected through questionnaires. Data analysis was carried out by univariate and bivariate analysis methods. The results showed that around 51.6% of adolescent boys at SMAN 1 Pangkalan Koto Baru experienced moderate acne vulgaris. Their level of personal hygiene was also categorized as moderate, with 69.4% of respondents having a similar level of hygiene. The results of the analysis showed a significant relationship between facial skin hygiene and the incidence of acne vulgaris in adolescent boys at SMAN 1 Pangkalan Koto (Sig. Pearson Chi-Square: 0.021 < 0.05).